Cybercrime Prevention for Students in TPQ Darul Muayyad Gunungpati - Dani Muhtada; Irawaty Irawaty; Dina Silvia Puteri (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2025)
The rapid advancement of digital technology and the increasing access to the internet among children and adolescents have raised concerns about their vulnerability to cybercrime. In Islamic educational settings, particularly among santri (Quranic students), exposure to digital platforms without adequate digital literacy or protection mechanisms can lead to significant risks. This research explores the extent of cybercrime awareness among santri and evaluates the preventive efforts taken by Islamic education institutions to safeguard their students. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation from selected Islamic schools. The study found that while many santri regularly access online content through mobile devices, their understanding of cyber threats such as online fraud, cyberbullying, and exposure to inappropriate content remains low. Most institutions lack structured programs for digital literacy or cyber safety education, and there is limited parental or institutional supervision of online activity. However, there is strong potential for integrating digital safety awareness into religious teachings, reinforcing values such as honesty, modesty, and responsibility in digital behavior. The study concludes that effective protection against cybercrime requires collaborative efforts involving educators, parents, and policymakers. Recommendations include the development of culturally relevant digital literacy modules, training for teachers, and community-based campaigns to raise awareness about cyber safety in religious contexts. This research highlights the urgent need to bridge the digital safety gap for Quranic students, ensuring their well-being in an increasingly connected world.